The Death Tradition of Malay Communities of Sungai Raya Dalam Village West Kalimantan - Mahdi, Mahdi (The Pontianak State Institute of Islamic Studies, 2018)
Islam and culture cannot be separated since there are already Shari'a provisions about certain thing. However, when the Shari'a is practiced, it needs human interpretatation to understand. So, it will show one form of culture. This paper describes the form of the Malay community tradition in West Kalimantan in welcoming death. In Islam, if someone dies, there is an obligation for the living person to bathe, forgive, overtake and bury. In addition to these provisions, in practice, in the midst of the Islamic community, Malays in Sungai Raya Dalam, there is a tradition of mourning, handling bodies, until tahlilan after the body is buried. This tradition shows how the local culture relates to Islam. At the same time, showing Islam and local culture complement each other in the space of life of the Malay community.